KNOWLEDGE AND BEHAVIOR CONCERNING PESTICIDE PACKAGING WASTE MANAGEMENT OF VEGETABLE GROWERS IN KHI LEK SUBDISTRICT, MUEANG DISTRICT, UBON RATCHATHANI PROVINCE - บุญขาว, ลักษณีย์; ผากา, พาวีนา (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2021)
This cross-sectional research aims to study the knowledge and behavior concerning pesticide packaging waste management among vegetable growers in Khi Lek Subdistrict, Mueang District, Ubon Ratchathani Province. The questionnaire was collected from 103 vegetable growers by accidental sampling method. Data were analyzed using frequency count and percentages. The study found that the most common type of pesticide packaging found in this area was glass bottles (90.29%). The vegetable growers’ knowledge of pesticide packaging waste management was good (93.20%). Their behavior toward pesticide packaging waste management was at the improvable level, 93.20%. Their improper practices included the disposal of pesticide packaging waste into municipal bins (28.16%), the lack of engagement in separating pesticide packaging waste from other wastes (16.51%), and the selling of pesticide packaging waste to junk shops (14.57%). This study found that the vegetable growers did not do the following: putting up a warning sign at the landfill (57.14%), destroying pesticide packaging waste (46.75%), sprinkling lime when depositing pesticide containers in the landfill (41.55%), and putting lime in the dump pit (40.26%). Therefore, the concerned agencies should promote positive behaviors toward pesticide packaging waste management for vegetable growers to reduce the impacts of pesticides on human health and the environment.